Counting the cost [videorecording] (The inside story host & producer, Loren Legarda., 1991)
History of the RP-US bases treaty; Views of the senators on the need to draw up a new bases pact; and A report about the U.S. bases already turned over or about to be turned over to Philippine authorities.